A Correlation of Glycemic Index and Macular Thickness After Phacoemulsification in Diabetics - Rajni Sethia; Parin K Mehta; Raghunandan Kothari; Vivan Desai; Avani Soni (Delhi Journal of Ophthalmology)
Purpose: To study the relationship between HbA1c and macular thickness using Optical coherence tomography (OCT). Methods: Prospective cohort study where 50 eyes of type 2 Diabetes mellitus patients with mild to moderate Non-Proliferative Diabetic Retinopathy (NPDR) were included. They underwent uncomplicated phacoemulsification surgery and were divided into 3 groups based on HbA1c levels - Group 1: <6.5%, Group 2: 6.5% - 8% and group 3: >8%. Nine macular subfields as defined by Early Treatment of Diabetic Retinopathy study (ETDRS) were measured using OCT The HbA1c level of each patient was measured and compared with the macular thickness as well as visual acuity. Result: No correlation of HbA1c level and central foveal thickness was found in our study (p=0.554). The change in visual acuity also had no correlation with HbA1c (p>0.05). There was a significant increase in central foveal thickness at 1 month postoperatively, irrespective of HbA1c level (p=0.002, p=0.001, p=0.005). Conclusion: HbA1c has no impact on central foveal thickness or BCVA. Diabetics undergoing phacoemulsification show a change in central foveal thickness post operative but that may not necessarily be due to uncontrolled diabetes.